Using ultrahigh‐resolution mass spectrometry and toxicity identification techniques to characterize the toxicity of oil sands process‐affected water: The case for classical naphthenic acids. (7th August 2017) - Hughes, Sarah A.; Mahaffey, Ashley; Shore, Bryon; Baker, Josh; Kilgour, Bruce; Brown, Christine; Peru, Kerry M.; Headley, John V.; Bailey, Howard C.
Abstract: Previous assessments of oil sands process‐affected water (OSPW) toxicity were hampered by lack of high‐resolution analytical analysis, use of nonstandard toxicity methods, and variability between OSPW samples. We integrated ultrahigh‐resolution mass spectrometry with a toxicity identification evaluation (TIE) approach to quantitatively identify the primary cause of acute toxicity of OSPW to rainbow trout ( Oncorhynchus mykiss ). The initial characterization of OSPW toxicity indicated that toxicity was associated with nonpolar organic compounds, and toxicant(s) were further isolated within a range of discrete methanol fractions that were then subjected to Orbitrap mass spectrometry to evaluate the contribution of naphthenic acid fraction compounds to toxicity. The results showed that toxicity was attributable to classical naphthenic acids, with the potency of individual compounds increasing as a function of carbon number. Notably, the mass of classical naphthenic acids present in OSPW was dominated by carbon numbers ≤16; however, toxicity was largely a function of classical naphthenic acids with ≥17 carbons. Additional experiments found that acute toxicity of the organic fraction was similar when tested at conductivities of 400 and 1800 μmhos/cm and that rainbow trout fry were more sensitive to the organic fraction than larval fathead minnows ( Pimephales promelas ). Collectively, the results will aid in developing treatment goals and targets for removal of OSPW toxicity in water return scenarios both during operations and on mine closure. Environ Toxicol Chem 2017;36:3148–3157. © 2017 SETAC Abstract : The aquatic toxicity of oil sands process‐affected water was isolated to the organic fraction using toxicity identification evaluation techniques. The organic fraction was then further fractionated into different percent methanol fractions and analyzed for toxicity and naphthenic acids using ultrahigh‐resolution Orbitrap mass spectrometry to confirm the potency of naphthenic acid species and identify those responsible for toxicity.